Impact of baby behaviour on caregiver's infant feeding decisions during the first 6 months of life: A systematic review - Mireya Vilar‐Compte; Rafael Pérez‐Escamilla; Dania Orta‐Aleman; Valeria Cruz‐Villalba; Sofía Segura‐Pérez; Kate Nyhan; Linda M. Richter (Wiley, 2022)
Abstract Caregivers are often concerned about baby behaviours. Without adequate counselling, parental response can lead to altering infant feeding and jeopardizing breastfeeding. We conducted a systematic review to assess the evidence about the influence of baby behaviours perceived as problematic (crying, sleep waking and posseting) on infant feeding decisions during the first 6 months of life (self‐reported milk insufficiency, breastfeeding duration and introduction of formula). The review focused on quantitative studies published in English, Portuguese or Spanish without date restriction. The search was designed with the support of a medical librarian and conducted in seven databases. Data were managed in Covidence and risk of bias was assessed through the Johanna Briggs Institute critical appraisal checklists. Synthesis of the literature was guided by a conceptual model of the impact of baby behaviours on caregivers feeding practices. We retrieved and reviewed 4312 titles/abstracts and selected 22 for review; 10 were purely descriptive and 12 were cross‐sectional, prospective and quasi‐experimental studies. Although studies from diverse regions were included in the review, more than half were from high‐income countries. All studies reported that baby behaviours affect feeding decisions, the most common baby behaviours studied were crying and fussiness, and the studies suggested relationships with lactation problems and reports of milk insufficiency, maternal breastfeeding confidence, breastfeeding duration and discontinuation, and introduction of formula. There are many factors that lead to perceiving baby behaviours as problematic and there is a need to provide anticipatory guidance to parents and caregivers, starting in pregnancy and counselling through well‐trained health providers.